Domestication of aromatic medicinal plants in Mexico: Agastache (Lamiaceae)-an ethnobotanical, morpho-physiological, and phytochemical analysis - Guadalupe Carrillo-Galván; Robert Bye; Luis E. Eguiarte; Sol Cristians; Pablo Pérez-López; Francisco Vergara-Silva; Mario Luna-Cavazos (BMC, 2020)
Abstract Background Most reports of domesticated plants that involve a domestication gradient or inter-specific hybridization in Mexico have focused on those used as food. This study provides knowledge about these processes in two aromatic medicinal plants, Agastache mexicana (Lamiaceae) and A. m. subsp. xolocotziana, widely used in Mexican traditional medicine for the treatment of gastrointestinal ailments and for their sedative effect. Different populations of A. mexicana along a gradient of domestication are found in the foothills of the Popocatepetl volcano of central Mexico, while in this same area the subsp. xolocotziana grows only in the cultivation, possibly a product of hybridization between A. mexicana and Agastache palmeri. This study links ethnobotanical, morpho-physiological, and phytochemical evidence to document the domestication of both taxa as well as elucidates the possible hybrid origin of the subsp. xolocotziana. Method We analyze three groups of data derived from (1) 80 semi-structured interviews aimed at documenting the selection criteria related to the use and management of A. mexicana; (2) a cultivation experiment under homogeneous conditions, evaluating 21 floral, vegetative, and seed characters (that were important according to ethnobotanical information) in 97 plants corresponding to 13 populations of the taxa under study; and (3) the chemical profiles of the essential oils of these plants by means of a thin-layer chromatography. Results By linking the three types of evidence, two evolutionary processes are distinguished: (1) A. mexicana occurs in the encouraged-cultivated phases of the domestication gradient and (2) A. m. subsp. xolocotziana may have originated through inbreeding depression or hybridization. These two cultivated plants show a domestication syndrome based upon organoleptic differentiation due to their dissimilar phytochemical composition and gigantism in flowers, seeds, and rhizomes (the last enhancing their asexual reproductive capacity). In addition to this, A. mexicana exhibits more intense floral pigmentation and foliar gigantism while subsp. xolocotziana presents floral albinism and partial seed sterility. Conclusion Two divergent evolutionary processes are reported for the domestication of A. mexicana as a result of the intensification of its use and management. The selection processes of these plants have resulted in alternation of the organoleptic properties based upon the divergence of the phytochemical composition. Also, gigantism has been selected in culturally preferred plant parts and in correlated structures. The preceding characteristics reinforce the joint use of these plants in infusion in Mexican traditionalmedicine for the treatment of gastrointestinal diseases and for their sedative effects.